PENERAPAN STRATEGI KOOPERATIF-KOLABORATIF DALAM PEMBELAJARAN MENULIS SURAT RESMI SISWA SMA - Kusubakti Andajani (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2009)
This study aimed to describe the improvement of business letter writing skills through the cooperative-collaborative strategy. The design employed the action research procedure by Kemmis and McTaggart (1988), consisting of plan, action, observation, and reflection. The subjects were Year XII students of the Language Program of SMAN 2 Batu. The data were collected through tests, observations, field notes, and interviews and analyzed by means of the qualitative descriptive technique. The results showed that business letter writing was one topic that the students could not master well. They wrote letters based on those the teacher presented because they did not know much about effective sentences, diction, and spelling. Therefore, they did not have creativity in writing letters. This problem was solved using the cooperative-collaborative strategy. Through this strategy, the students were more motivated to learn and the quality of the learning outcomes could be enhanced to the maximum.